OSCILLATORY SILICON AND ALUMINUM AQUEOUS CONCENTRATIONS DURING EXPERIMENTAL ALUMINOSILICATE WEATHERING - Faimon J. (My University, 1996)
Granodiorite, amphibolite, and feldspar samples were dissolved in acidic, neutral, and basic solutions under ambient conditions as laboratory batch experiments. Oscillations of silicon and aluminium concentrations in leaching solutions during long-term weathering of aluminosilicates have been observed. A simple kinetic nonlinear model, based on polymerization of soluble aluminosilicate, is proposed to explain the oscillatory behavior.